ORGANIZATIONAL AND FINANCIAL MECHANISM OF PUBLIC MANAGEMENT OF THE HEALTH CARE SYSTEM IN FOREIGN COUNTRIES - Aimagambetov Ye.B,; Tingisheva A., (Academic Journal of Physical and Chemical Sciences, 2019)
The article examines the health care system, selected on the basis of accounting for organizational and financial features: mainly state, mainly social - insurance, mostly private. Most clearly, these health systems are represented in the following countries: predominantly state, characterized by a significant role of the state - (United Kingdom, Greece, Denmark, Norway, Portugal, Sweden, etc.), predominantly social insurance - (Austria, Belgium, Netherlands, Germany, France , Switzerland, Japan), mainly private - (USA, South Korea, and others). The authors conducted a comparative analysis of the health care system in foreign countries. Identified organizational features of the management of the health care system, identified sources of financing health care in three types: budget, insurance, private. On the basis of the analysis made the appropriate conclusions. It should be noted that the study of the organizational and financial mechanism of the healthcare industry in foreign countries is necessary in order to be able to use the experience of countries with the most effective healthcare system in domestic practice.